Protein Interaction Prediction on PHI Networks Using Graph Convolution Networks - Koca, M. Burak; Karadeniz, Ilknur; Nourani, Esmaeil; Sevilgen, F. Erdogan (IEEE, 2021)
Proteins are biological molecules that play a critical role in vital biological processes. Interactions between pathogen proteins and host proteins form pathogen-host interaction (Pitt) networks. These bipartite interaction networks have great importance in determining which vital activities are affected by the pathogen and the diseases it may cause. Experimental detection of the protein interactions in wet labs is both time-consuming and costly. The limited number of experimentally detectable interactions and overlook of some potential interactions lead to development of computational methods. In this study, a graph convolution network (GCN) based method is presented that enables to predict protein-protein interactions in Pill networks. The unsupervised trained GCN model (GraphSAGE) uses amino acid sequences as node features as well as the topological information. This is the first study to the best of our knowledge which provides GCN models to do protein-protein interaction prediction in Pill networks. The experimental results show that the developed model performs 10% better than the state-of-art algorithms on the benchmark Pill dataset and it predicts interactions with 96% accuracy.
29th IEEE Conference on Signal Processing and Communications Applications (SIU) -- JUN 09-11, 2021 -- ELECTR NETWORK
Keywords: bioinformatics; protein-protein interaction prediction; PHI networks; graph convolution networks